Environmental Emissions 2021
DOI: 10.5772/intechopen.92389
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Soot Polymer Nanocomposites (CSPNCs): Production, Surface Morphological, Glass Transition Temperature Phenomenon and Optical Properties

Abstract: The present chapter covers the production and properties of carbon soot nanoparticles (CSNPCs) and their doped carbon soot polymer nanocomposites (CSPNCs). The first part of this chapter will provide a brief introduction of carbon soot, its morphology, production and synthesis methods. The second part will explain the investigation of carbon soot nanoparticles by flame deposition method and their properties. The third part will provide a short knowledge on polymer nanocomposites (PNCs) and their processing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…e existence of this peak, on the other hand, may be attributable to a water molecule absorbed by the KBr salt during sample preparation or spectral acquisition. e existence of tiny (sp 2 or sp 3 ) aromatic clusters of amorphous carbon soot is indicated by certain weak bands found at low wavenumbers 1,048 cm −1 and 669 cm −1 [69].…”
Section: Ftir Spectroscopy Study Of the Soot Depositsmentioning
confidence: 99%
“…e existence of this peak, on the other hand, may be attributable to a water molecule absorbed by the KBr salt during sample preparation or spectral acquisition. e existence of tiny (sp 2 or sp 3 ) aromatic clusters of amorphous carbon soot is indicated by certain weak bands found at low wavenumbers 1,048 cm −1 and 669 cm −1 [69].…”
Section: Ftir Spectroscopy Study Of the Soot Depositsmentioning
confidence: 99%
“…Numerous nano fillers can significantly enhance the thermophysical properties of polymer nanocomposites, enabling a wide range of commercial applications in industries like electronics, optics, energy, sensors, and healthcare [7][8][9][10][11]. Several studies have indicated [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] improved composite properties as a result of doping polymers with various nano fillers. The incorporation of carbon soot into polymers enhances their thermal conductivity and mechanical properties, such as tensile strength and hardness, making them suitable for applications where efficient heat dissipation is required.…”
Section: Introductionmentioning
confidence: 99%